Female and male patients' perceptions of primary care doctors' communication skills in Hong Kong - Vivienne Leung; Kimmy Cheng (The Beryl Institute, 2016)
This study examined how female and male patients perceive primary doctors' communication skills in the Chinese context. To do so, this study specifically investigates female and male patients' general perceptions toward primary care doctors' communication skills in medical consultations. Specifically, this study focused on (a) female and male patients' satisfaction level toward primary care doctors' communication skills in medical consultations (b) female and male patients' perception of the types of verbal and nonverbal communication skills applied by primary care doctors in medical consultations (c) as well as which gender of doctors with whom patients prefer to communicate during primary care medical consultations in Hong Kong. A purposive sampling survey of Hong Kong residents aged 18 or older was conducted in April 2014. A total of 450 completed questionnaires were received. All respondents have visited a public hospital for outpatient service in the past 2 years. Results showed that there were no patient gender differences in patients' perceptions of doctors' communication skills, both female and male patient respondents showed a preference for same-gender doctors. Interestingly, in contrast with prior research, male patient respondents in this study revealed a stronger preference for doctors of the same gender than female patient respondents did. Other differences, such as cultural norms, values and practices, rather than just gender differences, may account for patients' perceptions of doctors' communication skills.